Menyelidiki Peran Perceived Value dalam Mengintervensi Pengaruh E-Service Quality dan E- Recovery Service Quality terhadap Loyalty Intention (Studi pada Bukalapak) - Soni Tia Kurniawan; Teguh Widodo (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The purpose of this study is to investigate the role of perceived value in interfering with the influence of e-service quality and e-recovery service quality on Bukalapak users' loyalty intention. The population used in this study were all Bukalapak users in Indonesia. This study uses non probability sampling techniques by means of convenience sampling. The sample in this study amounted to 291 Bukalapak users. The technique of collecting data uses a questionnaire containing questions based on the variables studied. From the questionnaire obtained, the validity test, reliability test and Goodness-of-fitness test were conducted. The data analysis technique used in this research is structural equation modeling (SEM) LISREL 8.8. The results of the study conclude that: 1) e- service quality does not have a positive and significant effect on perceived value; 2) e-recovery service quality has a positive and significant effect on perceived value; 3) perceived value does not play a role in increasing the influence of e-service quality on loyalty intention; 4) e-service 1uality has a positive but not significant effect on loyalty intention; 5) perceived value has a positive and significant effect on loyalty intention; 6) e-recovery service quality has no significant positive effect on loyalty intention.